ANALISIS MORFOMETRIK UKURAN TUBUH KAMBING LOKAL UMUR PRA SAPIH YANG DI PELIHARA SECARA TRADISIONAL - Karsum Y Tagoi; Fahrul Ilham; Nibras Karnain Laya (Animal Husbandry Department, Faculty of Agriculture Gorontalo State University, 2020)
This study aims to determine body size and body size of pre-age old goat breeds traditionally maintained in Kabila Bone District, Bone Bolango District and to find out the local goat maintenance system applied by farmers in Kabila Bone District, Bone Bolango District. The research material was local goat aged pre-age from 1 week to 10 weeks as many as 30 individuals. This study used a survey method. Retrieval of data by purposive sampling and sample determination by accidental sampling. The data obtained were analyzed by calculating the mean, standard deviation, coefficient of variation, regression equation, and growth rate between age and body size. Based on the statistical results, the average value obtained was 8.62 cm head length, 6.92 cm head width, 9.47 cm head height, 15.16 cm chest width, 19.94 cm chest inside, 34.25 cm shoulder height, chest circumference 33.49 cm, body length 34.36 cm, canon circumference 6.31 cm and body size increase between age and head length is 0.056 cm.